2021
DOI: 10.1109/tnet.2020.3030543
|View full text |Cite
|
Sign up to set email alerts
|

Failure Resiliency With Only a Few Tunnels – Enabling Segment Routing for Traffic Engineering

Abstract: Traffic engineering is an important concept that allows Internet Service Providers (ISPs) to utilize their existing routing hardware more efficiently. One technology that can be used is Segment Routing (SR). In this paper, we address the use of SR to increase the resilience against failure scenarios. In addition, we develop solutions that are manageable and, thus, deployable in a tier 1 ISP network. We propose a post-convergence aware SR based optimization model. With it, we can proactively find a single SR co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The most professional practice, must first read the data stream, read the data stream, found that the car intake pressure sensor than other engines of the same model to a larger point, in addition to no other phenomenon. However, the intake pressure is associated with the exhaust system, according to which it is believed that the exhaust system is not smooth, and the successful handling of this fault [13][14].…”
Section: Methods Of Df Analysis In the Diagnosis Of Faults In The Ele...mentioning
confidence: 99%
“…The most professional practice, must first read the data stream, read the data stream, found that the car intake pressure sensor than other engines of the same model to a larger point, in addition to no other phenomenon. However, the intake pressure is associated with the exhaust system, according to which it is believed that the exhaust system is not smooth, and the successful handling of this fault [13][14].…”
Section: Methods Of Df Analysis In the Diagnosis Of Faults In The Ele...mentioning
confidence: 99%
“…Moreover, the researchers of Ref. [33] presented an effective failure resiliency framework and controlled the number of tunnels for TE in SR. These articles reflect the potential to improve network performance for TE in SR.…”
Section: Segment Routingmentioning
confidence: 99%
“…They provide examples where ECMP can decrease the quality of SR by creating congestion when combined with SR. In [17], Schüller et al propose an exact failure resilient MILP model that minimizes MLU based on the model from [2], but this model has very high computational costs. The only study combining jointly the optimization of segment paths and SPR weights is the work of Parham et al [15].…”
Section: Literature Reviewmentioning
confidence: 99%